Penentuan Kriteria Prioritas Pemilihan Supplier pada PT Inkor Bola Pacific dengan menggunakan Metode Fuzzy Analytic Hierarchy Process - Elizabeth Tania Febriani; Teguh Oktiarso (Jurnal Sains dan Aplikasi Keilmuan Teknik Industri (SAKTI), 2022)
PT Inkor Bola Pacific is a company that produces various types of balls according to the demand. However, the lack of a clear list of criteria for selecting suppliers has led to problems in fulfilling raw material needs. This research aims to identify the criteria that must be met to choose suppliers and determine priority criteria. The Fuzzy Analytical Hierarchy Process method is used to determine the weight of each criterion through assessments obtained from questionnaires. The assessment is converted into a Fuzzy scale and the paired matrix is calculated to determine the ranking of each criterion. The results show that the weight of quality is 0.7874 and the weight of price is 0.2126 for fast-moving raw materials. For slow-moving raw materials, quality is given a weight of 1. The prioritization of criteria helps the purchase department to choose suppliers according to the company's standards. The findings can contribute to improving the supply chain management of PT Inkor Bola Pacific and other companies in similar industries.